2000
DOI: 10.1002/1522-7278(2000)15:4<338::aid-tox10>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic study of organic and inorganic toxic substances onAllium cepa, Lactuca sativa, andHydra attenuata cells

Abstract: Assessment of genotoxicity using the micronucleus assay for demonstration of chromo-) ( some aberrations and the frequency of double nuclei in cells and cytotoxicity here changes in ) quantitative characteristics of nucleoli were measured as a parameter of cell metabolism for different organic and inorganic toxic substances was conducted with three organisms, namely, Allium cepa, Lactuca sativa,and Hydra attenuata. Comparative analyses and discussion of data along with results obtained on toxicity and mutageni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…A number of transgenic and bioassay techniques have been recommended for assessing the genotoxic effects of environmental pollutants on plants including random-amplified polymorphic DNAs (RAPDs), micronucleus (MCN) induction, or Comet assay (Steinkellner et al 1998;Angelis et al 2000;Arkhipchuk et al 2000;DeWolf et al 2004;Kovalchuk et al 2001;Liu et al 2005b).…”
Section: Metal Toxicity and Tolerancementioning
confidence: 99%
“…A number of transgenic and bioassay techniques have been recommended for assessing the genotoxic effects of environmental pollutants on plants including random-amplified polymorphic DNAs (RAPDs), micronucleus (MCN) induction, or Comet assay (Steinkellner et al 1998;Angelis et al 2000;Arkhipchuk et al 2000;DeWolf et al 2004;Kovalchuk et al 2001;Liu et al 2005b).…”
Section: Metal Toxicity and Tolerancementioning
confidence: 99%
“…A size variation of these nucleoli both inside one single cell and among the cells was also observed (Table 3, Figure 4 H-J). According to some scientists, the variation in the number of nucleoli in plants results from the action of genotoxic agents [73]. This study showed a substantial variation within the quantity of nucleoli in the A. cepa meristematic cells after exposure to the azo dye concentrations.…”
Section: Nor Bandingmentioning
confidence: 99%
“…Hydra bioassays have indeed been reported sensitive to a wide spectrum of contaminants of metallic, organic, or mixed origin (Blaise and Kusui 1997;Pardos et al 1999;Arkhipchuk et al 2000;Holdway 2005), as have cytotoxicity tests conducted with rainbow trout primary hepatocytes (Strmac and Braunbeck 2002;Finne et al 2007). Overall, these responses reflected slight acute (class II), acute (class III), and high acute (class IV) hazard indicating the presence of varying degrees of contamination in snow collected from these sites.…”
Section: Bioassay Resultsmentioning
confidence: 99%